2022
DOI: 10.1039/d2cy00506a
|View full text |Cite
|
Sign up to set email alerts
|

High coke deposition resistance by Cr loading on zeolite defects: reduced regeneration in cracking reactions

Abstract: A Cr-loaded zeolite cannot be considerably deactivated by coke deposition and can be reused for LDPE cracking without regeneration. The Cr species interact with hydroxyl groups derived from structural defects...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…These phenomena have already been reported by several studies including our previous research. [51,55] First, the effects of H 2 supply on coke deposition under toluene vapor were investigated using pristine beta. Subsequently, the amount of coke deposited was evaluated using TGA.…”
Section: Resultsmentioning
confidence: 99%
“…These phenomena have already been reported by several studies including our previous research. [51,55] First, the effects of H 2 supply on coke deposition under toluene vapor were investigated using pristine beta. Subsequently, the amount of coke deposited was evaluated using TGA.…”
Section: Resultsmentioning
confidence: 99%
“…We discovered that Cr-loaded zeolite catalysts were not significantly deactivated by coke during lowdensity polyethylene catalytic cracking. 57 During the reaction, the Cr 6+ species bonded to the silanol groups acted as catalysts for the dehydrogenation of light alkanes in the product, while aromatics were decomposed by hydrogenation at the zeolite acid site. It is difficult to introduce transition metal elements into the zeolite framework by direct synthesis because its ionic radius is greater than the silicate matrix.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Cr 6+ is known to exhibit dehydrogenation activity, and its oxide supported on zeolites promotes the dehydrogenation of light alkanes. We discovered that Cr-loaded zeolite catalysts were not significantly deactivated by coke during low-density polyethylene catalytic cracking . During the reaction, the Cr 6+ species bonded to the silanol groups acted as catalysts for the dehydrogenation of light alkanes in the product, while aromatics were decomposed by hydrogenation at the zeolite acid site.…”
Section: Introductionmentioning
confidence: 99%
“…A similar phenomenon was observed in our previous works. 15 The Cr 3+ and Cr 2+ species may not contribute to coke inhabitation. Mo-loaded samples exhibited bands in the range from 200 to 400 nm as shown in Fig.…”
mentioning
confidence: 99%
“…Our recent studies have revealed the modification of Cr on zeolite catalysts inhibited coke formation during some reactions, leading to improved catalytic lifetimes. 14,15 Thus, it can be expected to prolong the catalyst lifetime of Mo/ZSM-5 on the MDA reaction by adding Cr. In this study, Cr-modified Mo/ZSM-5 catalysts were prepared and applied to the MDA reaction.…”
mentioning
confidence: 99%